Culture et interculturel en psychologie : préférence pour la démarche scientifique et conséquences épistémologiques - Bertrand Troadec (Nantes Université, 2010)
Cross-cultural research is often defined as the study of cultural diversity or the study of cultural contacts. This definition opposes two designs of the relations between cultures (separation versus meeting). This opposition is not satisfactory from an anthropological and sociological point of view. Any culture, conceived as "separated" from the others, is always the product of "meetings" which occurred during History. Sociological analyses of racist ideologies differentiate racism of exclusion (separation) and racism of assimilation (meeting). Taking these analyses as a starting point, we propose to go beyond the preceding opposition. In sum, psychological cross-cultural research can be defined as a result of a complex system of relations between ideologies about races, ethnic groups, cultures, involving both separation and meeting.